Effect of soil amendments and irrigation regimes on minimum tillage planted sweet potato (Ipomoea batatas) in rice (Oryza sativa) fallows under lowland conditions - NEDUNCHEZHIYAN, M; SINHABABU, D P; SAHU, P K (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during the year 2008-09 and 2009-10 at Central Rice Research Institute, Cuttack, India to study the effects of soil amendments and frequency of irrigation on minimum tillage planted sweet potato (Ipomoea batatas L.) in rice (Oryza sativa L.) fallows under lowland conditions. The experiment was conducted in split plot design with soil amendments (rice straw, farmyard manure (FYM) and no amendment) in main plot and frequency of irrigation (no irrigation, 2, 3 and 4 irrigations) in sub plots. In minimum tillage planted sweet potato, application of rice straw and FYM increased sweet potato growth and root yield. Increasing number of irrigations also increased minimum tillage planted sweet potato growth and root yield. When rice straw was applied, three irrigations were found optimum, whereas in the case of FYM, four irrigations were required for higher root yield.